Reimagining informal STEM learning opportunities to foster STEM identity development in underserved learners - Çolakoğlu, Jasmin; Steegh, Anneke; Parchmann, Ilka (Frontiers in Education, 2023)
Informal science, technology, engineering, and mathematics (STEM) learning opportunities offer great potential to position learners as insiders to STEM and to foster their positive STEM identity development. Despite their goal to create equal insights and access to STEM learning for all, however, these informal STEM learning opportunities often fail to reach underserved students, hindering their STEM identity development and perpetuating inequity. To address this issue, out-of-school programs need to be designed with underserved students in mind, and concepts, as well as practical approaches that foster STEM identity development, need to be identified. In this article, we review 13 peer-reviewed publications that investigate informal STEM learning opportunities for underserved learners at a young age. We synthesize concepts such as competence, performance, recognition, supportive relationships, sense of belonging, agency, interest, and attitudes that influence underserved learners’ STEM identity development, and corresponding practical approaches such as personal relationships, role models, authentic settings, hands-on-activities, and non-stereotypical structures fostering agency. We also discuss theoretical frameworks for underserved learners’ STEM identity development. We suggest that recognition, a sense of belonging, supportive relationships, and agency play important roles in fostering STEM identity development in underserved students. The paper concludes with recommendations to change traditional patterns in informal and formal STEM education to empower underserved students to construct their own STEM identity as agentic individuals.